USE OF NONSTEROIDAL ANTI-INFLAMMATORY DRUGS AND BIOLOGICAL AGENTS FOR THE TREATMENT OF AXIAL SPONDYLOARTHRITIDES. RECOMMENDATIONS OF THE SPONDYLOARTHRITIS STUDY GROUP OF EXPERTS, ALL-RUSSIAN PUBLIC ORGANIZATION «THE ASSOCIATION OF RHEUMATOLOGY OF RUSSIA» - I. Z. Gaidukova; A. P. Rebrov; S. A. Lapshina; E. N. Otteva; T. V. Dubinina; V. V. Badokin; A. G. Bochkova; O. V. Bugrova; A. A. Godzenko; A. I. Dubikov; O. N. Ivanova; T. V. Korotaeva; et al. (Научно-практическая ревматология, 2017)
The paper gives recommendations for the drug therapy of axial spondyloarthritides, which have been developed by the Spondyloarthritis Study Group of Experts. The recommendations describe the patient management tactic in the most common clinical situations, which is aimed at maximizing the efficacy and safety of treatment.